High pressure and elastic properties of a guanidinium-formate hybrid perovskite. Issue 21 (18th May 2020) - Gao, Hongqiang; Li, Chao; Li, Linsui; Wei, Wenjuan; Tan, Yuhui; Tang, Yunzhi
Abstract : The structural anisotropy of [C(NH2 )3 ][Cd(HCOO)3 ] is regulated by guanidinium cation, and its orientation makes the young's modulus representation show a huge rigid response. Abstract : The high pressure and elastic properties of a hybrid ABX3 -type perovskite, [C(NH2 )3 ][Cd(HCOO)3 ] (CdGF), based on the A-site guest molecules are revealed via combining the high-pressure synchrotron X-ray diffraction experiments with density functional theory (DFT) calculations. The experimental results indicate that the anisotropic axial compressibilities are K a = 2.8(4) and K c = 20.9(10) TPa −1 within the pressure scope of 4.12 GPa, and calculations reveal the microscopic evolution of structure under pressure and demonstrate that this structural anisotropy is a consequence of the directional guest molecule and the cooperative effect of hydrogen bonding and octahedral tilting. In addition, full elastic constants of the perovskite were calculated to describe Young's moduli, shear moduli and Poisson's ratios. Notably, these discrete moduli are governed by the orientational guest molecule suggesting that the perovskite may display positive (negative) linear compression if it is flexible (rigid) along one principal axis.